The grammar of profit : the price revolution in intellectual context - Finkelstein, Andrea, 1949- (Brill's studies in intellectual history, 2006)
"This study explores the relationship between the prevailing concept of "just profit" and contemporary reactions to the Sixteenth-Century Price Revolution by tracing the evolving meaning of "profit" in religious, political, and social discourse. Using the period's own macrocosmic-microcosmic analogy, the book examines family correspondence, wills, and court cases in addition to formal tracts to move outward from issues of spiritual profit to family values, employment relationships, and church and state."--BOOK JACKET.